Water poisoning and resistance in catalytic oxidation of VOCs from industrial flue gas - Xiao Zhang; Da Chen; Cai Liang; Boxiong Shen (Fuel Processing Technology)
Volatile organic compounds (VOCs) emitted from industrial flue gas, as precursors to particulate matter and photochemical smog, pose direct hazards to atmospheric environment and adversely affect the health of communities. Catalytic oxidation is a cost-effective and feasible method for VOCs purification from industry flue gas, however, encounter catalyst poisoning caused by water vapor under realistic working environments. Understanding the influence of water vapor on VOCs catalytic oxidation activity and the water-involved mechanisms on metal oxide catalyst surfaces is crucial in solving water poisoning in catalytic reactions. This review concludes that various working conditions of industrial flue gas significantly influence the impact of water vapor on VOCs oxidation, in terms of efficiency, stability, and selectivity. Water-involved VOCs catalytic oxidation mechanisms, including: competitive adsorption, generation of hydroxyl, alter reaction path and cleaning effect, alongside the specific methods employed to study these processes are analyzed. This review also covers the developments in water-resistant catalysts, focusing on strategies such as optimizing catalyst supports, active components, morphologies, and preparation methods. This review aims to advance industrial flue gas purification by providing better understanding of mechanisms of VOCs oxidation in wet flue gas.